Victorian Short Stories of Troubled Marriages - Kipling, Rudyard, 1865-1936; D'Arcy, Ella, 1857-1937; Doyle, Arthur Conan, 1859-1930; Gissing, George, 1857-1903; Morrison, Arthur, 1863-1945 (Salt Lake City, UT : Project Gutenberg, 2005)
"Victorian Short Stories of Troubled Marriages" by Rudyard Kipling et al. is a collection of short stories written during the late 19th century. The anthology delves into the complexities and challenges of marital relationships in the Victorian era, exploring themes of infidelity, discord, and societal expectations. Through various narratives, readers can anticipate encountering troubled couples facing distinctive personal dilemmas and societal pressures. The opening of the book begins with "The Bronckhorst Divorce-Case," a story that presents the grim marriage of Bronckhorst, a coarse and disrespectful husband, and his devoted wife. As Bronckhorst's disdain for his wife manifests through cruel remarks and disregard for her feelings, it becomes evident that their marriage is fraught with tension. The narrative builds suspense as Bronckhorst accuses a man named Biel of pursuing his wife, leading to a court case that unveils deeper layers of conflict and betrayal. This story sets the tone for the collection, revealing the often profound sadness and intricate dynamics intertwined in troubled marriages during the Victorian period. (This is an automatically generated summary.)
The Bronckhorst Divorce-Case, by Rudyard Kipling -- Irremediable, by Ella D'Arcy -- "A Poor Stick," by Arthur Morrison -- The Adventure of the Abbey Grange, by Arthur Conan Doyle -- The Prize Lodger, by George Gissing.
Release date is 2005-03-26
E-text prepared by Juliet Sutherland, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Short stories, English